1964
DOI: 10.1128/jb.88.5.1493-1496.1964
|View full text |Cite
|
Sign up to set email alerts
|

VIRULENCE-LINKED COLONIAL AND MORPHOLOGICAL VARIATION IN LEPTOSPIRA

Abstract: colony typical hooked Leptospira icterohaemorrhagiae was virulent for hamsters and guinea pigs. On cultivation, it was gradually replaced by a serologically identical small-colony avirulent straight mutant. The hooked virulent form was selected in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
1

Year Published

1967
1967
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 3 publications
3
8
0
1
Order By: Relevance
“…It should be noted that similar linear motility mutants of L. interrogans have been obtained by others (9,21,23,24). Simpson and White reported differences in ultrastructure between linear and hook-shaped serovars (21).…”
Section: Fig 4 (A)supporting
confidence: 82%
“…It should be noted that similar linear motility mutants of L. interrogans have been obtained by others (9,21,23,24). Simpson and White reported differences in ultrastructure between linear and hook-shaped serovars (21).…”
Section: Fig 4 (A)supporting
confidence: 82%
“…In this situation colonial morphology could be associated with virulence. The avirulent, weakly motile, unhooked leptospires formed small colonies, whereas the virulent, motile, hooked leptospires formed large colonies (7). Similar results were obtained by Petrov and Chernukha (14) with serovar mozdok.…”
supporting
confidence: 87%
“…Johnson and Harris (8) showed that virulent leptospires were less susceptible than avirulent leptospires to the lethal action of serotypespecific immune antibcdy and complement, although the immune antibody cross-agglutinated completely (4,8). Thus, there is no obvious serological difference between virulent and avirulent leptospirae.…”
Section: Discussionmentioning
confidence: 99%
“…Leptospira Reference Laboratory, Dunedin, New Zealand. L. icterohaemorrlhagiae (GP) was the avirulent straight form of L. icterohaemorrhagiae (GP-B), hooked, and virulent for guinea-pigs (4) and 10-day chick embryos, freshly reisolated in culture after its second guinea pig passage. L. zanonii (-E), virulent (carrier state for mice; 3), was freshly reisolated from mice after its fifth mouse passage; its avirulent cultured line was L. zanioni.…”
Section: Methodsmentioning
confidence: 99%